Market share analysis of vitamin C products using the Markov chain method and marketing strategy using SOAR analysis - Pratama, Inggrid Bella; Aryanny, Enny (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Market Share is frequently used to indicate market competitiveness to record how well and rapidly a company is developing compared to its rivals. Vitamin products are presently a popular item among many consumers. 73% of Indonesians consumed many supplements during the Covid-19 virus pandemic, according to a survey conducted by PT Neurosensum Technology International, a market research firm based on neuroscience and artificial intelligence (AI) technology. The survey covered 500 sample sizes and found that 94% of respondents consumed vitamin C during a pandemic. According to data from Top Brand, the top five products from 2018 to 2022 are Vitacimin, Enervon-C, You C1000, Redoxon, and Vicee. It is a well-known fact that Vitamin C's market share fluctuates wildly from year to year. This study employs the Markov Chain and SOAR techniques to generate some alternative marketing strategies. The results indicated that the prediction of the percentage of market share until equilibrium conditions were reached was obtained in the 28th period of March 2025, with Vitacimin at 41%, Enervon C at 13%, You C1000 at 23%, Redoxon at 11%, and Vicee at 12%. The Redoxon product was then analyzed using SOAR analysis, and eight alternative marketing strategies were developed.